Cartoons and their impact on the process of socialization of children "A descriptive analytical study of a sample of children’s parents in the city of Lattakia" - جحجاح غزوان; يسرى زريقة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aims to study cartoons and their impact on the process of socialization of children. Therefore, the researcher used the descriptive analytical method and the questionnaire as a tool for data collection. The questionnaire was distributed to a sample of (383) individuals from the parents of Children in the city of Lattakia, and they were chosen randomly, and the questionnaire was applied between 3/5 to 20/5/2023, and the researcher verified its validity and stability by appropriate methods, and showed a number of results, some of which we mention: 1- There is no negative effect of cartoons on the social upbringing of the child according to the gender of the respondent. 2- There is no positive effect of cartoons on the social upbringing of children, according to their number in the family. 3- There is no negative effect of cartoons on the social upbringing of children due to the age of the children. 4- There is a negative effect of cartoons on the social upbringing of children due to the hours of watching.